Efektivitas Sistem Temu Kembali Informasi Perpustakaan Digital Institut Seni Indonesia (ISI) Yogyakarta dalam Tinjauan Recall dan Precision - Thoriq Tri Prabowo (Perpustakaan Nasional, 2021)
Today's digital library is a necessity. A system that provides all-digital information and services requires that all aspects of it should be accessed effectively. In the context of information retrieval in digital libraries, the information retrieval systems are important instruments. The system becomes a link between relevant information and its users. Evaluation of the information retrieval system to determine its effectiveness is important to ensure that users receive good retrieval services. Recall and precision are approaches to measure the effectiveness of information retrieval systems that are widely used. This study aims to determine the effectiveness of the ISI Yogyakarta digital library retrieval system based on recall and precision approaches. This study will provide benefits for librarians in knowing the effectiveness of the information retrieval system and the extent of their accuracy in indexing. This research uses an experimental method with a quantitative approach. The researcher chose a sample of the searching keywords purposively and then tested them by searching on the portal http://digilib.isi.ac.id/. The data obtained were analyzed using the formula recall and precision. In this study the subjects tested were interior design subjects. The precision measurement of 10 keywords on the subject of interior design gets 92.37% results while the recall measurement gets 80.79% results. The result stated that precision is higher than recall, it showed that the information retrieval system of ISI Yogyakarta’s digital library is quite effective.